«Ne pas traduire, c'est traduire encore». Et si la non-traduction était un procédé de traduction ? - Bocquet, Catherine A. (Studia Romanica Posnaniensia, 2017)
This paper shows the manifold aspects of the non-translation phenomenon : besides shortened and summarized versions, which alter the source text in a quantitative way, non-translation can also have a qualitative effect, for instance when sociocultural references are erased. If non-translation is an infringement of the translator's duties, in some cases it can be a very fruitful solution. There is a lack of literature on the subject, and although it is often mentioned briefly, this phenomenon has never been tackled seriously.